Prevalence of Workplace Health Practices and Policies in Hospitals: Results From the Workplace Health in America Study. Issue 8 (November 2020) - Mulder, Laura; Belay, Brook; Mukhtar, Qaiser; Lang, Jason E.; Harris, Diane; Onufrak, Stephen
Purpose: To provide a nationally representative description on the prevalences of policies, practices, programs, and supports relating to worksite wellness in US hospitals. Design: Cross-sectional, self-report of hospitals participating in Workplace Health in America (WHA) survey from November 2016 through September 2017. Setting: Hospitals across the United States. Participants: Random sample of 338 eligible hospitals participating in the WHA survey. Measures: We used previous items from the 2004 National Worksite Health Promotion survey. Key measures included presence of Worksite Health Promotion programs, evidence-based strategies, health screenings, disease management programs, incentives, work-life policies, barriers to health promotion program implementation, and occupational safety and health. Analysis: Independent variables included hospital characteristics (eg, size). Dependent characteristics included worksite health promotion components. Descriptive statistics and χ 2 analyses were used. Results: Eighty-two percent of hospitals offered a wellness programs during the previous year with larger hospitals more likely than smaller hospitals to offer programs ( P < .01). Among hospitals with wellness programs, 69% offered nutrition programs, 74% offered physical activity (PA) programs, and 84% had a policy to restrict all tobacco use. Among those with cafeterias or vending machines, 40% had a policy for healthier foods. Only 47% and 25% of hospitals offered lactation support or healthy sleep programs, respectively. Conclusion: Most hospitals offer wellness programs. However, there remain hospitals that do not offer wellness programs. Among those that have wellness programs, most offer supports for nutrition, PA, and tobacco control. Few hospitals offered programs on healthy sleep or lactation support.